The Roles of 27 Genera of Human Gut Microbiota in Ischemic Heart Disease, Type 2 Diabetes Mellitus, and Their Risk Factors: A Mendelian Randomization Study. Issue 9 (25th May 2018) - Yang, Qian; Lin, Shi Lin; Kwok, Man Ki; Leung, Gabriel M; Schooling, C Mary
Abstract: Manipulation of the gut microbiota presents a new opportunity to combat chronic diseases. Randomized controlled trials of probiotics suggest some associations with adiposity, lipids, and insulin resistance, but to our knowledge no trials with "hard" outcomes have been conducted. We used separate-sample Mendelian randomization to obtain estimates of the associations of 27 genera of gut microbiota with ischemic heart disease, type 2 diabetes mellitus, adiposity, lipid levels, and insulin resistance, based on summary data from CARDIoGRAAMplusC4D and other consortia. Among the 27 genera, a 1-allele increase in single nucleotide polymorphisms related to greater abundance of Bifidobacterium was associated with lower risk of ischemic heart disease (odds ratio = 0.985, 95% confidence interval (CI): 0.971, 1.000; P = 0.04), a 0.011–standard-deviation lower body mass index (95% CI: −0.017, −0.005), and a 0.026–standard-deviation higher low-density lipoprotein cholesterol level (95% CI: 0.019, 0.033), but the findings were not robust to exclusion of potential pleiotropy. We also identified Acidaminococcus, Aggregatibacter, Anaerostipes, Blautia, Desulfovibrio, Dorea, and Faecalibacterium as being nominally associated with type 2 diabetes mellitus or other risk factors. Results from our study indicate that these 8 genera of gut microbiota should be given priority in future research relating the gut microbiome to ischemic heart disease and its risk factors.